The 2024 revised clinical guidelines on the management of thyroid tumors by the Japan Association of Endocrine Surgery - Iwao Sugitani; Naomi Kiyota; Yasuhiro Ito; Naoyoshi Onoda; Tomo Hiromasa; Kiyomi Horiuchi; Seigo Kinuya; Tetsuo Kondo; Sueyoshi Moritani; Kiminori Sugino; Hisato Hara (Endocrine Journal)
The Japan Association of Endocrine Surgery published the first edition of the “Clinical guidelines on the management of thyroid tumors” in 2010 and the revised edition in 2018. The guideline presented herein is the English translation of the revised third edition, issued in 2024. The aim is to enhance health outcomes for patients suffering from thyroid tumors by facilitating evidence-based shared decision-making between healthcare providers and patients, as well as standardizing the management of thyroid tumors. The focus is on adult patients with thyroid tumors, addressing clinically significant issues categorized into areas such as an overview of the diagnosis and treatment of thyroid nodules, treatment strategies by histological type, radioactive iodine therapy, treatment of advanced differentiated carcinoma, pharmacotherapy, and complications and safety management associated with thyroid surgery. Thirty-two clinical questions were established in these areas. Following a comprehensive search of the literature and systematic review to evaluate the overall evidence, we aimed to present optimal recommendations by considering the balance of benefits and harms from the patient’s perspective. We integrated evidence and clinical experience to determine the “Certainty of evidence” and “Strength of recommendations”. Based on these, we illustrated overall flows of care as “Clinical algorithms”. Necessary background knowledge of diseases and established clinical procedures for understanding the recommendations are presented in “Notes”, while information that may be clinically useful but for which evidence remains insufficient is included in “Columns”, based on the current state of evidence. Finally, future challenges for the next revision are presented as “Future research questions”.